2017
DOI: 10.1002/jcc.24727
|View full text |Cite
|
Sign up to set email alerts
|

Phage‐like packing structures with mean field sequence dependence

Abstract: Summary Packing of double-stranded DNA in phages must overcome both electrostatic repulsions and the problem of persistence length. We consider coarse-grained models with the ability to kink and with randomly generated disorder. We show that the introduction of kinking into configurations of the DNA polymer packaged within spherical confinement results in significant reductions of the overall energies and pressures. We employ a kink model which has the ability to deform every 24 bp, close to the average length… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
6
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 57 publications
1
6
0
Order By: Relevance
“…Both external and internal DNA were usually condensed to form a globule that, when internal, sometimes had branches (e.g., iCe particle at upper right in Figure 3a). The branches suggested that the packaged DNA had folds (kinks), as previously suggested by both data [24] and computer simulation [25]. Although C particles were best seen in cells and sub-cellular vesicles that were cytoplasm-deficient, both ϕ and C particles were sometimes seen, although less distinctly, while in cells with cytoplasm not detectably leaked (Figure 3b).…”
Section: Phage-sized Particlessupporting
confidence: 67%
“…Both external and internal DNA were usually condensed to form a globule that, when internal, sometimes had branches (e.g., iCe particle at upper right in Figure 3a). The branches suggested that the packaged DNA had folds (kinks), as previously suggested by both data [24] and computer simulation [25]. Although C particles were best seen in cells and sub-cellular vesicles that were cytoplasm-deficient, both ϕ and C particles were sometimes seen, although less distinctly, while in cells with cytoplasm not detectably leaked (Figure 3b).…”
Section: Phage-sized Particlessupporting
confidence: 67%
“…Assuming axial symmetry, the solution is an spool [20]. However, relaxing the symmetry constraints might lead to more complex structures such as those seen in experiments [7,9], theory [11,12], and simulations [15,16,18]. Indeed, as we show later, a single-domain spool is almost never the lowest elastic energy configuration.…”
mentioning
confidence: 80%
“…Packing into icosahedral capsids was shown to have a strong stochastic component [16], and structures without spool-like symmetry have been reported, including multidomain spool packing, observed when DNA is pushed into the capsid through a portal [17]. The effect of elastic kinks on packing has been discussed in [18], while local liquid-crystalline order of compacted DNA was found to play a crucial role promoting the formation of knots [19].…”
mentioning
confidence: 99%
“…[5] Okamoto and Ichiye present studies on proteins under high pressure, [6] [7] Dominy investigates the effect from metal ion in tumor Endothelial Marker 8 and Anthrax Protective Antigen, [8] and Pettitt explores phage-like packing structures with mean field sequence dependence. [9] Levy, Matubayasi and co-workers use an auxiliary (implicit solvent and vacuum) free energy surface to estimate, at a fraction of the computational cost, conformational free energy differences in explicit solvent for a couple of exemplar systems. [10] For protein-ligand interactions, CHARMM-based molecular docking is used by Armen and co-workers to study the binding modes of positive allosteric modulators and to rationalize the slow dissociation kinetics.…”
Section: Introductionmentioning
confidence: 99%
“…Mohammadiarani and Vashisth use, in their study, metadynamics to investigate the folding thermodynamics of an insulin peptide mimetic, which they discover has a strong helical propensity . Okamoto and Ichiye present studies on proteins under high pressure, Dominy investigates the effect from metal ion in tumor Endothelial Marker 8 and Anthrax Protective Antigen, and Pettitt explores phage‐like packing structures with mean field sequence dependence . Levy, Matubayasi and co‐workers use an auxiliary (implicit solvent and vacuum) free energy surface to estimate, at a fraction of the computational cost, conformational free energy differences in explicit solvent for a couple of exemplar systems …”
mentioning
confidence: 99%